Directive Utterances In The Sign Of The Four By Sir Arthur Conan Doyle: A Pragmatic Perspective - Damayanti, Afnita, Dr. Maryadi, M.A, Dra. Siti Zuhriah Ariatmi, M.Hum (2014)
This research aims at (1) describing the sentence types of directive utterances, (2) analyzing the intentions of directive utterances based on illocutionary act, and (3) analyzing the politeness strategy of directive utterances found in The Sign of the Four novel. This research applies descriptive method. The data are utterances containing directive utterances in The Sign of the Four novel. In collecting the data, the researcher uses documentation method by reading, classifying, underlining the data, and coding the data. To describe the sentence types, the researcher uses the theory of Frank, to find the intention the researcher refers to the theory of Searle, and clarifying the politeness strategy the researcher uses the theory of Brown and Lavinson. The result of this study shows that: (1) the sentence types of directive utterances used in The Sign of the Four novel are 63,63% data of imperative sentence, 27,27% data of interrogative sentence, and 9% data of declarative sentence. (2) the intentions of directive utterance are 57,57% data of the directive commanding category, 30,3% data of the directive requesting category, 15,15% data of the directive suggesting category, and 3,03% data of the directive warning category. The last is (3) politeness strategy of directive utterance, the researcher finds 24,24% data of the bald on record strategy, 21,21% data of the positive politeness strategy, 54,54% data of the negative politeness strategy, and 0% data of the off record strategy.